NARATIVE REVIEW: POTENSI INULIN UMBI DAHLIA SEBAGAI ANTI DIABETES - Sunarti Sunarti; Chrismis Novalinda Ginting; Sahna Ferdinand Ginting (Jurnal Keperawatan Priority, 2022)
Inulin is a type of polysaccharide that is commonly found in nature derived from the dahlia tuber plant, and other plants such as chicory, Jerusalem artichoke, Yaco´n potato and asparagus. Inulin is widely used in industry and pharmaceuticals. In the industrial world, inulin is used as a source of natural sweetener, enhances the taste of food, ferments, and is a low-fiber food source. While in the pharmaceutical world, inulin can be used in several studies, one of which is as an anti-diabetic. This study aims to determine the potential of dahlia tuber inulin as an anti-diabetic. The type of research is a narrative review. Search data using three databases, namely Elsevier (SCOPUS), Pubmed and Google Scholar with a limitation of the last 10 years of articles with the keyword "inulin for diabetes", with the PRISMA method. The results showed that inulin works on glucose absorption in the intestine, lowers blood sugar levels, lowers hemoglobin A1c, increases circulating GLP-1, reduces hyperglycemia, reduces insulin resistance (IR) and hyperlipidemia, reduces oxidative stress, increases insulin and leptin levels, facilitates glucose transport of GLUT4 by activating the PI3K/Akt pathway, is anti-inflammatory, and is involved in the expression of several anti-hyperglycemic genes. The conclusion is that dahlia tuber inulin has an anti-diabetic effect.